Clinical and Nonclinical Effects on Operative Duration: Evidence from a Database on Thoracic Surgery. (10th February 2020) - Wang, Jin; Cabrera, Javier; Tsui, Kwok-Leung; Guo, Hainan; Bakker, Monique; Kostis, John B.
Abstract : Background . Due to the high maintenance costs, it is critical to make full use of operating rooms (ORs). Operative duration is an important factor that guides research on surgery scheduling. Clinical effects, for example, surgery type, rationally influences operative duration. In this study, we also investigate whether the planning and scheduling decisions in ORs influence the operative duration. Methods . For our study, we collected and reviewed data on 2, 451 thoracic operations from a large hospital in China. The study was conducted over a period of 34 months. Linear and nonlinear regression models were used to detect the effects on the duration of the operations. We have also examined interactions between the factors. Results . Operative duration decreased with the number of operations a surgeon performed in a day (P < 0.001 ). It was also found that operative duration decreased with the number of operations allocated to an OR, as long as there were not more than four surgeries per day (P < 0.001 ). However, they increased with the number of operations if it was more than four (P < 0.01 ). The duration of surgery was affected by its position in the sequencing of surgeries performed by a surgeon. In addition, the effects of surgeons depend on the surgery type as well as the position in the sequencing order. Conclusions . Operative duration was affected not only due to clinical effects but also some nonclinical effects. Scheduling decisions significantly influenced operative duration.